Structural flexibility of the macrophage dengue virus receptor CLEC5A: implications for ligand binding and signaling. - Watson, A; Lebedev, A; Hall, B; Fenton-May, A; Vagin, A; Dejnirattisai, W; Felce, J; Mongkolsapaya, J; Palma, A; Liu, Y; Feizi, T; Screaton, G; et al. (2011)
The human C-type lectin-like molecule CLEC5A is a critical macrophage receptor for dengue virus. The binding of dengue virus to CLEC5A triggers signaling through the associated adapter molecule DAP12, stimulating proinflammatory cytokine release. We have crystallized an informative ensemble of CLEC5A structural conformers at 1.9-Å resolution and demonstrate how an on-off extension to a β-sheet acts as a binary switch regulating the flexibility of the molecule. This structural information together with molecular dynamics simulations suggests a mechanism whereby extracellular events may be transmitted through the membrane and influence DAP12 signaling. We demonstrate that CLEC5A is homodimeric at the cell surface and binds to dengue virus serotypes 1-4. We used blotting experiments, surface analyses, glycan microarray, and docking studies to investigate the ligand binding potential of CLEC5A with particular respect to dengue virus. This study provides a rational foundation for understanding the dengue virus-macrophage interaction and the role of CLEC5A in dengue virus-induced lethal disease.